Impact of clinical supervision on job satisfaction and emotional competence of nurses - Inês Alves da Rocha e Silva Rocha; Cristina Maria Correia Barroso Pinto; António Luís Rodrigues Faria de Carvalho (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: To evaluate the impact of implementing the SafeCare clinical supervision model on nurses' job satisfaction and emotional competence profile. Methods: This is a quasi-experimental study, with a sample of 28 nurses from a hospital in northern Portugal. A self-administered questionnaire was applied, used as pre and post-test, which included: sociodemographic and professional characterization; "Job Satisfaction Scale"; and "Veiga Emotional Competence Scale". We conducted descriptive statistical analysis and the Wilcoxon Test. Results: A significant decrease in the nurses' satisfaction with hierarchical superior was observed in the post-test. No significant differences were found in the nurses' job satisfaction and emotional competence after the implementation of the SafeCare Model. Conclusion: The SafeCare Model needs improvement, suggesting increasing the amount of training time administered to nurses and strengthening the healthcare institution's link to the Model.